Synthesis of biopolymer stabilized CeO2 nanoparticles and preparation of Chitosan-CeO2 nanocomposite hydrogels: A bifunctional material with photocatalytic activity and antimicrobial application. - Pyarasani - Pyarasani; Radha (2023)
2 Another objective of the proposal was to evaluate cerium nanocomposite hydrogels for antimicrobial application by inhibition zone test using gram-positive and gram-negative bacteria. TOTAL The proposed antibacterial studies was carried out using PNIPAM-KGM-CeO2 nanocomposite hydrogel and PNIPAM-CMC-CeO2 nanocomposite hydrogels. Different formulations of PNIPAM hydrogels obtained in the task 3 were used to study the antibacterial activity. the results of the study were not effective in inhibiting the growth of gram negative bacteria E.Coli and gram positive bacteria s.auerus. the possible reason for the poor antibacterial effect could be due to dense crosslinking of PNIPAM with the biopolymer KGM or CMC, the cerium nanoparticles incorporated into the hydrogel were completly trapped inside the hydrogel matrix which could have inhibited the liberation of cerium nanoparticles into the culture medium. 3 the other objective of the proposed work was to study the antibacterial application of synthesised cerium Nanoparticles. TOTAL as proposed in the project ,1st and 2nd year was to synthesize biopolymer capped cerium Nanoparticles and characterize the obtained Nanoparticles and look for the potential applications. in this regard we proposed to evaluate biopolymer capped cerium NPS for antimicrobial activity. for this antimicrobial activity, we utilized KGM capped Cerium NPS and CMC capped Cerium NPs prepared in different conditions. and 3 different strains of Staphylococcus aureus and 1 fungal strain of candida.albicans.The results of these work were very interesting, cerium nanoparticles synthesised at basic pH 9 and higher temperature 70°C were very effective in inhibiting antimicrobial growth. similarly Cerium NPS prepared at Basic pH11 and lower temperature 30°C showed high antimicrobial activity. cerium nanoparticles were effective upto 99% in inhibiting the growth of bacteria and fungal strains. Manuscript of this work is ready to communicate a peer reviewed journal by 15 of NOV 2022. 4 Another objective of ...